If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 0.5x + -0.9 = -0.4x Reorder the terms: -0.9 + 0.5x = -0.4x Solving -0.9 + 0.5x = -0.4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '0.4x' to each side of the equation. -0.9 + 0.5x + 0.4x = -0.4x + 0.4x Combine like terms: 0.5x + 0.4x = 0.9x -0.9 + 0.9x = -0.4x + 0.4x Combine like terms: -0.4x + 0.4x = 0.0 -0.9 + 0.9x = 0.0 Add '0.9' to each side of the equation. -0.9 + 0.9 + 0.9x = 0.0 + 0.9 Combine like terms: -0.9 + 0.9 = 0.0 0.0 + 0.9x = 0.0 + 0.9 0.9x = 0.0 + 0.9 Combine like terms: 0.0 + 0.9 = 0.9 0.9x = 0.9 Divide each side by '0.9'. x = 1 Simplifying x = 1
| -4=-4(x-7) | | 42+28= | | 8x+21=13-6x | | -18+2x=64 | | v^2-4v^1-21=0 | | 36+84= | | Cos(x)=0.19 | | 6x+4(2x+6)=94 | | -4x+(5x-7)=2 | | 17x+9=3x-33 | | (2x+5)(6x^2+6x+4)= | | y=5+16 | | 16+5n=-7(6+8n)+3 | | 3(4+9)= | | 1+5x-13=140 | | 4=6y-1 | | v^2+10+24= | | 10+8n=117 | | (2/3p^4r^2)(r^2z^5)(9p^3z^2) | | 2x+-4=3x-4 | | 5x+9y+y+2x-y-15= | | 0=6y-1 | | 4(3d-2)-8d=-5 | | 2x^2-9x=100 | | 3600=150-3.75x | | -6x-9=2-7x | | 2x^2-10x=6x^2-11x | | 7.5x+2.5=20+2.5x | | 5x+9x=14x | | 15s=12 | | 3x-8+x-1+6=21 | | 6h+5=52 |